Use the additive inverse to find -12 2/3 - -8 5/6 Write the answer as a mixed number.

1 answer

To find the sum, we subtract the second operand (the negative term) from the first operand:

-12 2/3 - (-8 5/6)

The additive inverse of -8 5/6 is 8 5/6. So, we can rewrite the expression as:

-12 2/3 + 8 5/6

To perform addition, we need to have a common denominator for the two fractions:

The common denominator is 6, so we convert -12 2/3 and 8 5/6 to fractions with denominators of 6.

-12 2/3 = -38/3
8 5/6 = 53/6

Now, we can add the two fractions together:

-38/3 + 53/6

To add these fractions, we need to have a common denominator. The least common multiple of 3 and 6 is 6.

So, we convert the fractions to have a denominator of 6:

(-38/3) * (2/2) = -76/6 = -38/3
53/6

Now that the fractions have a common denominator, we can add them together:

-38/3 + 53/6 = (-38 + 53)/6 = 15/6

Next, we simplify the resulting fraction:

15/6 = 5/2

Since the fraction is larger than 1, we can rewrite it as a mixed number:

5/2 = 2 1/2

Therefore, -12 2/3 - -8 5/6 equals 2 1/2.